2010
DOI: 10.3346/jkms.2010.25.2.293
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Knee Osteoarthritis in Elderly Community Residents in Korea

Abstract: The purpose of this study was to estimate the prevalence of radiographic and symptomatic knee osteoarthritis (OA) among community residents and to elucidate the relevant risk factors. This prospective, population-based study was conducted on residents over 50 yr of age in Chuncheon. Subjects completed an interview based on a standardized questionnaire and clinical evaluation including standardized weight bearing semiflexed knee A-P radiographs. We defined a subject with the Kellgren and Lawrence grade ≥2 as ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
80
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 13 publications
9
80
1
5
Order By: Relevance
“…Similar to findings from other parts of the world, knee OA was more prevalent among women compared with men and increased with age [10,14,15]. The prevalence of symptomatic knee OA was significantly higher than that in Beijing and Shantou (16.05% vs. 9.60%/8.3-10.8%) [16,17], while lower than that in Wuchuan county of inner Mongolia with nonsignificant difference (16.05% vs. 19.21%) [11].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to findings from other parts of the world, knee OA was more prevalent among women compared with men and increased with age [10,14,15]. The prevalence of symptomatic knee OA was significantly higher than that in Beijing and Shantou (16.05% vs. 9.60%/8.3-10.8%) [16,17], while lower than that in Wuchuan county of inner Mongolia with nonsignificant difference (16.05% vs. 19.21%) [11].…”
Section: Discussionsupporting
confidence: 84%
“…In addition women are more susceptible to obesity than men which are another important risk factor for OA. This is consistent with previous reports of Sudo, et al, (2008) and Sanjeev, & Michael, (2012) who revealed that knee OA was more common among females than males.Concerning the level of education, the present study revealed that post/secondary was prevailing among less than half of the patients, this finding in the same line with Kim et al, (2010) who stated that knee OA is significantly greater with a good level of education. Also this is in agreement with The Center for Disease Control and Prevention (CDC, 2010) which reported that the incidence of knee OA in people with high education more than in people of illiteracy.…”
Section: Discussionsupporting
confidence: 80%
“…The development of OA is a multifactorial process associated with a variety of risk factors, including genetic predispositions, aging, obesity, inflammation, and excessive mechanical loading. In Korea, radiographic and symptomatic knee OA affects 37.3% and 24.2% of elderly individuals, respectively 1. Given the high morbidity and huge economic and personal burdens of OA, there is an urgent need for defining the pathogenesis that contributes to OA development.…”
mentioning
confidence: 99%